Retraction Note: Risk factors, clinical presentations and predictors of stroke among adult patients admitted to stroke unit of Jimma university medical center, south west Ethiopia: prospective observational study - Ginenus Fekadu; Legese Chelkeba; Ayantu Kebede (BMC Neurology, 2019)
The Editor and Publisher have retracted this article [1]. This article was published as the result of a technical error which resulted in two versions [1, 2] of the same article being published. [2] is the final version of the article. Springer Nature apologises to the authors and to readers for the inconvenience caused. All authors agree with this retraction.